The Effects of Digital Marketing, Social Media Engagement, and Customer Trust on Customer Loyalty in an E-Commerce Contex - Hotmaria Pasaribu; Dwi Fany Fransiska Dewi Butar Butar; Hafni Cholida Nasution (Global Insights in Management and Economic Research, 2025)
Purpose of the study: In the highly competitive e-commerce landscape, customer loyalty has become a critical factor for long-term business success. This study examines the influence of digital marketing, social media engagement, and customer trust on e-commerce customer loyalty at PT. Kopi Bintang Indonesia (Tomoro Coffee). Materials and methods: The research aims to determine the individual and collective effects of digital marketing, social media engagement, and customer trust on e-commerce customer loyalty at PT. Kopi Bintang Indonesia. Results: The multiple linear regression analysis yielded the equation Y = 35.540 + 0.130X1 + 0.202X2 + 0.284X3 + e. Partial t-tests revealed that digital marketing (t = 3.310, p < 0.05), social media engagement (t = 5.270, p < 0.05), and customer trust (t = 6.748, p < 0.05) each had a positive and significant effect on customer loyalty. The simultaneous F-test (F = 50.223, p < 0.05) demonstrated that all three variables collectively exerted a significant influence on customer loyalty. The adjusted R² value of 0.606 indicated that 60.6% of the variance in customer loyalty could be explained by these three independent variables, with the remaining 39.4% attributable to factors outside the model. Conclusions: Digital marketing, social media engagement, and customer trust significantly influence e-commerce customer loyalty both individually and collectively. Companies should implement integrated strategies that enhance digital marketing quality, foster active social media interactions, and build customer trust through transparent communication and secure transactions to strengthen customer loyalty in the e-commerce environment.